Assessing the Impact of Employee Communication and HR Initiatives on Individual Performance - Maya Lestari; Ika Nurul Qamari; Siti Dyah Handayani (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
Communication is needed in every company activity as a means that can encourage employees to improve performance. Apart from communication, the lack of positive Human Resources (HR) initiatives within the company can result in alienation among employees. It is important for organizations to combine communication and the effectiveness of HR practices into one coherent form in facing challenges and improving employee work performance. Individual Work Performance (IWP) in a company is an important aspect for leaders in the process of achieving company goals. Individual Work Performance (IWP) measurements need to be carried out periodically to find out whether the business is achieving company goals and as a benchmark for making improvements to achieve the set goals. This research aims to analyze the influence of employee communication and the perceived effectiveness of HR initiatives on Individual Work Performance (IWP), which consists of three main elements, namely task performance, contextual performance and counterproductive work behavior. The method in this research is quantitative research using a questionnaire totaling 100 respondents with data processing using SmartPLS. The subjects in this research were employees of the Gunungkidul Regency Education, Youth and Sports Office. The results of the analysis in this study show that employee communication is proven to influence all elements of Individual Work Performance, namely task performance, contextual performance and counterproductive work behavior, whereas the perceived effectiveness of HR initiatives is proven to only influence one element of Individual Work Performance, namely contextual performance.